(untitled) (Praxis Educativa, 2021)
The creation of the General Administration of Physical Education (Dirección General de Educación Física) in 1938 implied profound transformations in the organization and in the disciplinary approach of this subject in Argentina. In order to unify criteria, this state agency implemented – during its almost ten years of existence – a series of innovative actions and strategies to professionalize its agents according to the guidelines of the national Physical Education. However, this federalizing strategy with strong chauvinist rhetorical imprints occurred in parallel with different initiatives that tended to a progressive internationalization of its policies. The survey of official documents that recorded the multiple exchanges and disciplinary actions at an internal and continental level provide a good X-ray of how – diachronically and sometimes synchronously –, the borders of national and international Physical Education were rethought when the so-called “Década Infame” (“Infamous Decade”) ended in Argentina.